The Native Speaker in Italian-Dialects Bilingualism: Insights From the Acquisition of Vicentino by Preschool Children - Sanfelici, Emanuela; Roch, Maja (Frontiers in Psychology, 2021)
This paper investigates the bilingualism originating from the native competence of a standard language (Italian) and a vernacular non-standardized local dialect (henceforth, bilectalism). We report results on the comprehension and production of narrative stories by 44 three- to five-year-old typically developing children exposed to both Italian and Vicentino from birth. Our findings show that all children produced and comprehended Italian. As for the dialect, children can comprehend Vicentino, despite not producing any dialectal element. The study further revealed an implicational scale in dialectal competence: if a child exhibits some productions with dialectal syntax, s/he also produces dialects at the phonological, morphological, and lexical levels. These findings are in line with the dialectological studies on adult speakers: dialectal competence should be arranged along a fine-grained continuum and the dialectal speaker should be considered as a multi-factorial notion. Our study extends this observation to children’s dialectal acquisition.